Recent studies on age determination of Indian fishes using scales, otoliths and other hard parts - Seshappa, G (Indian Journal of Fisheries, 2011)
At present it is customary to use the growth rings found in the scales, otolithsor other hard parts of fishes to assess the age at different periods of their lives.Though such rings were sometimes discovered in the past in India also, theywere rejected in view of the absence of clear summers and winters in our watersas occurring in temperate waters where clear growth differences are knownin the fishes and in their above said hard parts. Examination of the scalesof Cynoglossus semifasciatus Day at Calicut in the middle of this centuryproved not only the annual periodicity of the ring formation but also the causesof the same. Such rings or annuli were later found in the other species ofCynoglossus at Calicut and also in many other fishes elsewhere by otherworkers, though in a few cases there were difficulties because of the occasionaloccurrence of abnormalities and false checks in the scales, making theinterpretations a bit difficult. Later, coverage of more species from differentcentres revealed the widespread occurrence of growth rings (also called annuli)caused by factors other than seasons alone and their usefulness in agedeterminations. In the present paper the recent developments made in indiain this discipline of fishery biology are briefly reviewed.